Ablation loading of solid target through foam absorber on ABC laser at ENEA-Frascati. (March 2016) - De Angelis, R.; Consoli, F.; Gus'kov, S. Yu.; Rupasov, A.A.; Andreoli, P.; Cristofari, G.; Giorgio, G. Di; Giulietti, D.; Cantono, G.; Kalal, M.
Abstract: This work reports an experimental characterization of the efficiency of energy transmission of porous laser absorbers as a function of their density and thickness. In this campaign the foams were deposited on different metal substrates, which finally absorbed the energy deposited by the laser on the bulk of the porous material. The dimensions of the craters produced on the substrate can be related to the energy transmitted through the foams.